Effect and Complications of Everolimus Use for Giant Cardiac Rhabdomyomas with Neonatal Tuberous Sclerosis - Shibata, Yuka (AJP Rep, 2019)
Most cardiac rhabdomyomas with tuberous sclerosis (TS) are asymptomatic and spontaneously regress. However, some cases require surgical intervention due to arrhythmia and severe obstruction of cardiac inflow or outflow. We report herein a neonatal case of giant cardiac rhabdomyomas with TS and insufficient pulmonary blood flow from the right ventricle. Lipoprostaglandin E1 was necessary to maintain patency of the ductus arteriosus. We used everolimus, a mammalian target of rapamycin inhibitor, to diminish the cardiac rhabdomyomas. After treatment, the rhabdomyomas shrank rapidly, but the serum concentration of everolimus increased sharply (maximum serum trough level: 76.1 ng/mL) and induced complications including pulmonary hemorrhage, liver dysfunction, and acne. After the everolimus level decreased, the complications resolved. Everolimus may be a viable treatment option for rhabdomyomas, but its concentration requires close monitoring to circumvent complications associated with its use.